2012
DOI: 10.1039/c2lc20893h
|View full text |Cite
|
Sign up to set email alerts
|

A digital microfluidic method for multiplexed cell-based apoptosis assays

Abstract: Digital microfluidics (DMF), a fluid-handling technique in which picolitre-microlitre droplets are manipulated electrostatically on an array of electrodes, has recently become popular for applications in chemistry and biology. DMF devices are reconfigurable, have no moving parts, and are compatible with conventional high-throughput screening infrastructure (e.g., multiwell plate readers). For these and other reasons, digital microfluidics has been touted as being a potentially useful new tool for applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 54 publications
(65 reference statements)
0
77
0
Order By: Relevance
“…At 4 h after seeding in microgels, viability was B100%; while at 24 h after seeding, viability was B80%. The effects of electrostatic actuation on cell health were not explicitly evaluated here, but previous studies with 2D adherent or suspension cell culture have reported no or negligible effects on cell viability/morphology 24,45 or gene expression 46 when compared with non-actuated cells (as the electrical field drops across the insulating layer rather than droplets containing cells). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 4 h after seeding in microgels, viability was B100%; while at 24 h after seeding, viability was B80%. The effects of electrostatic actuation on cell health were not explicitly evaluated here, but previous studies with 2D adherent or suspension cell culture have reported no or negligible effects on cell viability/morphology 24,45 or gene expression 46 when compared with non-actuated cells (as the electrical field drops across the insulating layer rather than droplets containing cells). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that DMF, which has been previously reported to be useful for gentle handling of weakly adhered apoptotic cells 24 , might also be useful for non-disruptive reagent delivery to cell constructs grown in 3D microgels. The results in .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key mechanisms is that the droplet contact angle depends on the electric field applied between the droplet and the chip surface. Recently, DMF has been applied in the study of cell apoptosis as a function of staurosporine concentration, achieving a 33-fold reduction in reagent consumption compared with conventional methods [65]. Another advantage of DMF is that it is compatible with conventional high-throughput screening instruments, but it can result in lower detection limits and larger dynamic range because apoptotic cells are much less likely to delaminate when exposed to droplet manipulation by DMF relative to pipetting/aspiration in multiwell plates.…”
Section: Droplet Mode High-throughput Screeningmentioning
confidence: 99%
“…38 DMF enables facile control over many different reagents for multi-step processes, a property that has been useful for enzyme assays 27,[39][40][41] and for applications involving cells. [42][43][44][45][46][47][48][49][50][51] In these initial applications, enzymatic bioreactors and cell culture and assays were implemented in homogeneous aqueous droplets manipulated by DMF. We propose that the marriage of DMF with hydrogels represents a welcome combination for forming miniaturized enzyme bioreactors and 3D cell culture scaffolds.…”
mentioning
confidence: 99%